2010
DOI: 10.1177/1553350610384405
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Hemostatic Devices for Severe Liver Bleeding: A Randomized Controlled Animal Study

Abstract: BoCo showed significantly better hemostatic effect than PECo and OxCe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…In a head-to-head trial, TachoSil was compared with a regenerated oxidized cellulose compress (Surgicel, Johnson and Johnson, Somerville, NJ) and a bovine collagen-based compress (Sangustop, B. Braun Aesculap AG, Tuttlingen, Germany) [28]. Liver resection margins were created in a swine model and each of the three compresses applied to different areas of resection margin.…”
Section: Resultsmentioning
confidence: 99%
“…In a head-to-head trial, TachoSil was compared with a regenerated oxidized cellulose compress (Surgicel, Johnson and Johnson, Somerville, NJ) and a bovine collagen-based compress (Sangustop, B. Braun Aesculap AG, Tuttlingen, Germany) [28]. Liver resection margins were created in a swine model and each of the three compresses applied to different areas of resection margin.…”
Section: Resultsmentioning
confidence: 99%
“…In a study on bovine, Takács et al [16] observed less time to hemostasis in TachoSil in comparison to Surgicel. In our study, bleeding after hemostasis and mean first postoperative day blood drainage volume in TachoSil were significantly lower than Surgicel.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a drop-out rate of 5 %, a total number of 126 patients are needed to be enrolled. The expected difference of 15 % was justified by preclinical data [20]. …”
Section: Methodsmentioning
confidence: 99%